Implementasi Program Sertifikasi Guru dalam peningkatan Mutu Pendidikan - Nurhafni ' (Universitas Riau, 2011)
Teacher certification application practice in Nangroe Aceh Darussalam, however, facesmany obstacles that caused derived from conflict and tsunami which killed and wiped 2.500teachers, even though 5,429 substitute teachers has available in early 2006, only 30% who consid-ered appropriates for teaching. This long period of multicrisis and tsunami resulted, many ob-stacles to implement this program. According to data 2007, in Nort Aceh regency, from 11,981teachers, both permanent and temporary, only 4000 teachers who hold post graduate and diploma4. Study objective were to analyze teacher certification implementation that intended to improveteacher quality and to indentify stakeholder interest beyond this program. Descriptive-qualitativeanalysis and explorative qualitative methods, informan taken from institution for giving a guarantedof education quality,training far teaching education, education department of Nort Aceh, headmaster, and the teacher passed with a certification, informan is choiced with purposive sampling.Data analysis and interpretation result reveal that teacher certification program had substanceshifting from professionalism to prosperity improvement, hence certification remain not signifi-cantly influence the quality improvement, This shows that this program was not reflecting goodpolitical will to improve teacher professionalism. this program was intended to prosperity improve-ment. Therefore, it is suggested that goverment should not generalizes that all teacher mustprofessional. it will highly wise if intended to increase teacher prosperity than enhancing salary asmuch half main fee can be performed, and another half given to those who work professionally.